2013
DOI: 10.5194/acp-13-6065-2013
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of dust aerosols in the infrared from IASI and comparison with PARASOL, MODIS, MISR, CALIOP, and AERONET observations

Abstract: Infrared Atmospheric Sounder Interferometer (IASI) observations covering the period from July 2007 to December 2011 are interpreted in terms of monthly mean, 1°×1°, 10 μm dust Aerosol Optical Depth (AOD), mean altitude and coarse mode effective radius. The geographical study area includes the northern tropical Atlantic and the northwest Arabian Sea, both characterised by strong, regular dust events. The method developed relies on the construction of Look-Up-Tables computed for a large selection o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
83
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 52 publications
10
83
4
Order By: Relevance
“…Peyridieu et al (2013) reported similar values for the same data set. In this study for LMD over ocean, a bias of −0.922 km (−0.501 km) against the CALIOP geometric mean (cumulative extinction) height is found for data recorded during the day overpasses with a standard deviation of 1.142 km (1.409 km).…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Peyridieu et al (2013) reported similar values for the same data set. In this study for LMD over ocean, a bias of −0.922 km (−0.501 km) against the CALIOP geometric mean (cumulative extinction) height is found for data recorded during the day overpasses with a standard deviation of 1.142 km (1.409 km).…”
Section: Discussionsupporting
confidence: 70%
“…For the night overpasses the differences are −0.674 km (0.352 km) and the standard deviation 0.878 (1.180) ( Table 3). One reason for the larger spread in this study may be the use of monthly and spatially averaged data by Peyridieu et al (2013) and Capelle et al (2014), while here the comparison is made on a pixelby-pixel basis. Hence, extreme values are not averaged out.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations